Modifikasi Pupuk Urea Pelepasan Terkendali dan Pengaruhnya terhadap Lingkungan: Modification of Controlled Release Urea Fertilizer and Its Effect on the Environment - Jayanudin Jayanudin; Retno S.D. Lestari; Muhammad Luthfi; Maulana Suyuti (Jurnal Teknologi Lingkungan, 2022)
Controlled release urea fertilizer is one solution to increase the efficiency of nutrient absorption by plants and is more environmentally friendly. The aims of this study was to determine the yield and water absorption of controlled release urea fertilizer and analyze the content of nitrate, nitrite, and ammonia as environmental pollution parameters. Controlled release urea fertilizer was prepared using the emulsion crosslinking method with chitosan as the matrix. Urea was dissolved in chitosan then added in oil and stirred to form an emulsion. Next, glutaraldehyde saturated toluene (GST) as a crosslinker was dripped slowly and then continuously stirred for 2 hours. Urea loaded-chitosan microspheres (controlled release urea fertilizer) were dried and analyzed. Furthermore, the yield, water absorption, and analysis of nitrate, nitrite, and ammonia from the released urea was determined. Controlled release urea fertilizer obtained yield was 91.3–97.28%, water absorption of 78.87–91.61%. Analysis of nitrate, nitrite, and ammonia from the study concluded that urea fertilizer contained in chitosan microspheres is more environmentally friendly. Keywords: Controlled release urea, Chitosan, Environmentally friendly, Emulsion crosslinking, Fertilizer ABSTRAK Pupuk urea pelepasan terkendali merupakan salah satu solusi untuk meningkatkan efisiensi penyerapan nutrisi oleh tanaman dan lebih ramah lingkungan. Tujuan penelitian ini adalah menentukan yield dan daya serap air dari pupuk urea pelepasan terkendali dan analisis kandungan nitrat, nitrit, dan amonia sebagai parameter pencemaran lingkungan. Pupuk urea pelepasan lambat dibuat menggunakan metode crosslink emulsi dengan kitosan sebagai matriksnya. Urea dilarutkan dalam larutan kitosan kemudian dimasukkan ke dalam minyak dan diaduk untuk membentuk emulsi. Selanjutnya, glutaraldehyde saturated toluene (GST) sebagai crosslinker diteteskan secara perlahan dan terus diaduk selama 2 jam. Kitosan mikrosfer berisi urea (pupuk urea pelepasan terkendali) dikeringkan dan dianalisis. Selanjutnya, menentukan yield, daya serap air, dan menganalisis nitrat, nitrit, dan amonia dari hasil urea yang rilis. Pupuk urea pelepasan terkendali diperoleh yield sebesar 91,3–97,28%, daya serap air sebesar 78,87–91,61% . Analisis nitrat, nitrit, dan amonia dari pupuk menyimpulkan bahwa pupuk urea pelepasan terkendali lebih ramah lingkungan. Kata kunci: Urea pelepasan terkendali, Kitosan, Ramah lingkungan, Crosslink emulsi, Pupuk